A 68-Nucleotide Sequence within the 3′ Noncoding Region of Simian Hemorrhagic Fever Virus Negative-Strand RNA Binds to Four MA104 Cell Proteins - Hwang, You-Kyung (American Society for Microbiology, 1998)
The 3′ noncoding region (NCR) of the negative-strand RNA [3′(−)NCR RNA] of the arterivirus simian hemorrhagic fever virus (SHFV) is 209 nucleotides (nt) in length. Since this 3′ region, designated 3′(−)209, is the site of initiation of full-length positive-strand RNA and is the template for the synthesis of the 5′ leader sequence, which is found on both full-length and subgenomic mRNAs, it is likely to contain cis-acting signals for RNA synthesis and to interact with cellular and viral proteins to form replication complexes. Gel mobility shift assays showed that cellular proteins in MA104 S100 cytoplasmic extracts formed two complexes with the SHFV 3′(−)209 RNA, and results from competition gel mobility shift assays demonstrated that these interactions were specific. Four proteins with molecular masses of 103, 86, 55, and 36 kDa were detected in UV-induced cross-linking assays, and three of these proteins (103, 55, and 36 kDa) were also detected by Northwestern blotting assays. Identical gel mobility shift and UV-induced cross-linking patterns were obtained with uninfected and SHFV-infected extracts, indicating that the four proteins detected are cellular, not viral, proteins. The binding sites for the four cellular proteins were mapped to the region between nt 117 and 184 (68-nt sequence) from the 3′ end of the SHFV negative-strand RNA. This 68-nt sequence was predicted to form two stem-loops, SL4 and SL5. The 3′(−)NCR RNA of another arterivirus, lactate dehydrogenase-elevating virus C (LDV-C), competed with the SHFV 3′(−)209 RNA in competition gel mobility shift assays. UV-induced cross-linking assays showed that four MA104 cellular proteins with the same molecular masses as those that bind to the SHFV 3′(−)209 RNA also bind to the LDV-C 3′(−)NCR RNA and equine arteritis virus 3′(−)NCR RNA. However, each of these viral RNAs also bound to an additional MA104 protein. The binding sites for the MA104 cellular proteins were shown to be located in similar positions in the LDV-C 3′(−)NCR and SHFV 3′(−)209 RNAs. These data suggest that the binding sites for a set of the cellular proteins are conserved in all arterivirus RNAs and that these cell proteins may be utilized as components of viral replication complexes.